Desenvolvimento de chatterbots educacionais: um estudo de caso voltado ao ensino de algoritmos - Lemos, Elizama das Chagas (2014)
In development of Synthetic Agents for Education, the doubt still resides about what would be a behavior that could be considered, in fact, plausible for this agent's type, which can be considered as effective on the transmission of the knowledge by the agent and the function of emotions this process. The purpose of this labor has an investigative nature in an attempt to discover what aspects are important for this behavior consistent and practical development of a chatterbot with the function of virtual tutor, within the context of learning algorithms. In this study, we explained the agents' basics, Intelligent Tutoring Systems, bots, chatterbots and how these systems need to provide credibility to report on their behavior. Models of emotions, personality and humor to computational agents are also covered, as well as previous studies by other researchers at the area. After that, the prototype is detailed, the research conducted, a summary of results achieved, the architectural model of the system, vision of computing and macro view of the features implemented.